الاكتئاب لدى النساء خلال فترة انقطاع الطمث وعلاقته ببعض المتغيرات الديموغرافية / مركز إدارة زاخو المستقلة نموذجا - Hamoud Haji, Eman; Sami Muhammad, Zahid; Osman Ramadhan, Raad (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2025)
Menopause represents a natural physiological transition accompanied by complex psychological disorders resulting from acute hormonal changes and declining estrogen levels. This research aims to identify depression levels among women with menopausal disorders in the Zakho Independent Administration and analyze its relationship with demographic variables such as age, educational attainment, health status, and economic satisfaction. The study adopted a descriptive analytical methodology using the Beck Depression Inventory (BDI) on a sample of 75 housewives during menopause. Instrument validity was established through internal consistency method, and results showed high reliability coefficient (0.953) and depression levels above the hypothetical mean among sample participants. Depression severity was distributed as follows: 12% early signs of depression, 16% mild depression, 20% moderate depression, 27% severe depression, and 12% very severe depression. Results revealed statistically significant differences according to age group (40-49 years), educational attainment (favoring less educated women), and health status (favoring those with chronic illnesses). No significant differences were found regarding economic satisfaction. The study recommends designing specialized cognitive-behavioral psychological intervention programs for this population and training medical staff to detect early symptoms of depression.